Public Libraries as Incubators for Social Inclusion and Entrepreneurship for Achieving Sustainable Development Goals (SDGs) : A Progressive Transformation - Haryanto, Haryanto; Laugu, Nurdin; Zulaikha, Sri Rohyati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to exploreÂ the roleÂ of public libraries as incubators of social inclusion and entrepreneurship in supporting the achievement of the Sustainable Development Goals (SDGs). This study employed a qualitative approach with a case study method, focusing on public libraries in Karanganyar Regency, Central Java, Indonesia, that have implemented social inclusion and entrepreneurship programs. The data were collected through in-depth interviews with librarians, program participants, and relevant stakeholders, as well as direct observation and program document analysis. The data analysis followed the framework proposed by Miles and Huberman, which involves a systematic approach to qualitative data analysis, including data reduction, data display, and conclusion drawing/verification. The results showed that libraries functioning as entrepreneurship incubators can effectively provide platforms for business training, technology access, and network development. These programs enhanced individual's skills and knowledge and drived local economic growth by creating new businesses and increasing employment opportunities. Additionally, library social inclusion initiatives boost community participation and engagement, strengthen social cohesion, and reduce inequality. The research concludes that public libraries in Karanganyar Regency have significant potential as agents of social change by integrating social inclusion and entrepreneurship programs. To optimize this role, adequate policy support, enhanced librarian competencies, and collaboration with various stakeholders are necessary. Thus, libraries can significantly contribute to achieving the SDGs, particularly in quality education, decent work and economic growth, reduced inequalities, and partnerships for the goals.